Best Answer

The answer to the question, as stated, is that it is a quadratic equation in one unknown, x.

The solution to the equation is as follows:

x2 - 6x - 7 = 0 ie x2 - 7x + x - 7 = 0 or x(x-7) +1(x-7) = 0

(x+1)(x-7) = 0 so that x+1 = 0 or x-7 = 0 and so x = -1 or x = 7.

Q: What is x2 - 6x - 7 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x2 + 6x = 7 ⇒ x2 + 6x + 9 = 7 + 9 ⇒ (x + 3)2 = 16 ⇒ x + 3 = ±4 ⇒ x = -7 or 1

y = x2 - 6x + 2 y = x2 - 6x + 9 - 7 y = (x - 3)2 - 7

7 - 6x- x2 = 0 so changing signs and reordering, x2 + 6x - 7 = 0 then x2 + 7x - x - 7 = 0 that is x(x + 7) - 1(x + 7) = 0 so that (x - 1)*(x + 7) = 0 which implies that x - 1 = 0 ie x = 1 or x + 7 = 0 ie x = -7

x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0

x2 - 14x = -49 ∴ x2 - 14x + 49 = 0 ∴ (x - 7)2 = 0 ∴ x = 7

Related questions

A quadratic equation. If you wish to solve for x, you can do so as follows: -x2 + 6x + 7 = 0 x2 - 6x - 7 = 0 (x - 7)(x + 1) = 0 x ∈ {-1, 7}

x-intercept happens when y=0 0=x2+6x-7 0=(x - 1)(x + 7) x-intercepts are x=1 and -7

x2 + 6x = 7 ⇒ x2 + 6x + 9 = 7 + 9 ⇒ (x + 3)2 = 16 ⇒ x + 3 = ±4 ⇒ x = -7 or 1

y = x2 - 6x + 2 y = x2 - 6x + 9 - 7 y = (x - 3)2 - 7

x2+6x-7 = 0 (x+3)2-7 = 0 (x+3)2-7-9 = 0 (x+3)2 = 16 x+3 = + or - 4 x = - 3 + or - 4 x = 1 or -7

x^2+6x+2=9 x^2+6x-7=0 (x+7)(x-1)=0 x=-6,1 for your roots

7 - 6x- x2 = 0 so changing signs and reordering, x2 + 6x - 7 = 0 then x2 + 7x - x - 7 = 0 that is x(x + 7) - 1(x + 7) = 0 so that (x - 1)*(x + 7) = 0 which implies that x - 1 = 0 ie x = 1 or x + 7 = 0 ie x = -7

x²+6x+9=49 x²+6x-40=0 x1=-6/2 - Square root of ((6/2)²+40) x1=-3 - 7 x1= -10 x2=-6/2 + Square root of ((6/2)²+40) x2=-3 + 7 x2= 4

x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0

xx+3x+7=6x+18 xx+3x+7-(6x+18)=6x+18-(6x+18) xx-3x-11=0 Factors of -11: 1,-11 -1,11 Doesn't factor evenly, use quadratic

x2+6x-7 = (x+7)(x-1) when factored

x=1 and x=-7 are.